A little princess - Burnett H. Frances; Davison, Susanna; Aldous, Kate (England : Usborne Publication, 2005)
"A Little Princess" centers on Sara Crewe, a wealthy and imaginative girl at boarding school whose life takes a turn when she loses her fortune. Despite facing poverty and mistreatment, Sara's resilience, kindness, and imaginative spirit shine through, impacting everyone around her.
Young Sara Crewe, once wealthy at boarding school, faces tough times when her luck changes. Yet, her kind heart and vivid imagination help her and others through it all. Location: 3A
Keywords: Little princess